Development of Google Sites-Based Digital Teaching Materials for Indonesian Language Literacy Skills in Elementary Schools - Sukmawati Ishak; Akhmad Qomaru Zaman; Rarasaning Satianingsih (Elementary Teacher Education Program, Majalengka University, 2026)
Twenty-first-century learning requires the mastery of basic literacy skills from an early age. However, the utilization of interactive technology and teaching materials in elementary schools remains highly limited, especially in archipelagic areas with minimal digital infrastructure access. Therefore, this study aims to develop an effective, practical, and valid Google Site-based digital teaching material to improve the Indonesian language literacy skills of fourth-grade students at SD Negeri 29 Kabupaten Raja Ampat. The research method used is Research and Development (R&D), adapting the modified Borg and Gall model into six continuous stages. The trial was conducted directly on 30 students to evaluate user responses and learning outcomes improvement. The development results indicate that this product is highly valid and practical, capable of presenting multimodal materials (text, images, videos) in a structured manner with a low-bandwidth interface design. Empirically, the use of this teaching material is proven effective and significantly improves students' literacy skills. This is characterized by an escalation in the final average scores for fluent reading by 30%, reading comprehension by 38%, and writing simple responses by 38%. In conclusion, the Google Site-based digital teaching material is proven highly effective and feasible to be implemented as an innovative solution to overcome the limited literacy learning resources sustainably in elementary education, particularly in frontier, outermost, and underdeveloped (3T) areas. Keywords: Digital teaching materials; Google Site; literacy skills; elementary school; Indonesian language